The Effect of Schedule Thinning on Student Behavior During the Caught Being Good Game. Issue 3 (May 2023) - Bohan, Clare; Smyth, Sinéad
The Caught Being Good Game (CBGG) is a classroom management intervention which is described as a variation of the classic Good Behavior Game (GBG). It is based on the principle of positive reinforcement, such that teams of students can earn points for following the class rules during the game. Points are awarded by the teacher at different intervals during the game and these intervals were the focus of the current study. We aimed to determine if the CBGG is effective with an initially dense schedule of reinforcement which is progressively thinned. The efficacy of the CBGG in targeting academic engagement and disruptive behavior was demonstrated for one primary school class and for two target students in that class. The game remained effective when the reinforcement schedule was thinned from 2 minutes, up to 5 minutes. This has potential implications for teacher time saving while playing the game.